Influence of the coefficient of restitution on the clasiffication of granite sand using and elutriator - Borsa, Eugenia (2021)
The objective of this work was to measure the coefficient of restitution of fine granite sand dust (passing sieve ASTM N°30) and to study its influence on the prediction of classification parameters in an elutriator device. Three types of restitution coefficients were evaluated in the computational fluid dynamic model: experimental, elastic, and half the experimental value. The influence of process variables, such as the inclination angle of the equipment and the air inlet velocity, on the efficiency of the obtained fine and coarse fractions was also studied. The results indicate that the coefficient of restitution significantly influences the efficiency parameters calculated for the inclined tests, given the greater contact that exists between the particles and the equipment wall. The experimental value of the coefficient achieved almost total congruence with the coarse fraction collected for the tested velocities. For the vertical tests, the variation of the coefficient did not show significant differences for both collected fractions. The results obtained in this work allowed to gain a deeper insight into the studied gas-solid systems, and to improve the numerical predictions on fine particles classification processes widely used in the ceramic, mining and metallurgical industries.